AI-Driven Automation and Industrial Peace in Indonesia: Mediation Effects of Employability and Organizational Support - Athiyyah Riri Syahfitri; Zdzislaw Polkowski; Majid A. Nawaz; Abu Taha Zamani (WISE Pendidikan Indonesia, 2026)
This study explores the impact of AI-driven automation on job insecurity and industrial peace in Indonesia, emphasizing the mediating roles of employability and perceived organizational support (POS). As technological advancements reshape industries, employees face heightened uncertainties regarding their job security, which can undermine workplace harmony. This research utilizes a quantitative approach with data collected from 1,072 employees across various sectors in Indonesia, employing Structural Equation Modeling (SEM) to analyze the relationships among the key constructs. The findings reveal that AI-driven automation significantly increases job insecurity, which in turn negatively affects industrial peace. However, employability and POS serve as important mediators in these relationships, reducing the adverse effects of job insecurity and enhancing industrial peace. These results underscore the importance of reskilling initiatives and organizational support in maintaining a harmonious work environment during technological transitions. The study provides valuable insights for organizations navigating automation challenges and contributes to the broader literature on industrial relations and human resource management in the context of emerging technologies.